Irreversible binding of zomepirac to plasma protein in vitro and in vivo. - Smith, P C (1986)
Zomepirac is a nonsteroidal anti-inflammatory drug recently withdrawn from use because of an unexplained high incidence of immunological reactions. It is metabolized in humans to a reactive, unstable acyl glucuronide which accumulates in plasma. Because of the similarity of zomepirac glucuronide to bilirubin glucuronide in structure and stability and the documented irreversible binding of bilirubin to albumin through its acyl glucuronide, we studied the reaction of zomepirac acyl glucuronide with albumin in vitro from pH 5 to 9 and in vivo in six healthy human volunteers who had received a single 100-mg oral dose of zomepirac. Irreversible binding of zomepirac to protein was determined by exhaustive washing of protein, followed by hydrolysis of bound zomepirac-protein adduct with base, extraction of the liberated drug, and chromatographic measurement. Irreversible binding was observed both in vitro and in vivo. The extent of binding in vitro was time- and pH-dependent. In vitro drug binding was also observed for the isomers of zomepirac glucuronide which were formed by intramolecular acyl migration. Irreversible binding in vivo correlated with overall exposure to zomepirac glucuronide when exposure was expressed as the area under the plasma concentration vs. time curve. When probenecid (500 mg, twice daily), which decreases the plasma clearance of zomepirac glucuronide, was administered concurrently with zomepirac, irreversible binding of zomepirac was increased. The nature of the zomepirac protein binding is probably covalent. Formation of irreversibly protein-bound zomepirac occurs via the acyl glucuronide as previously shown for bilirubin glucuronide, and the reaction may be general for other drugs that are metabolized to acyl glucuronides.